PENGUKURAN KEEFEKTIFAN MESIN LOHIA 1 MENGGUNAKAN METODE TOTAL PRODUCTIVE MAINTENANCE (TPM) DI PT. KERTA RAJASA RAYA, PLANT MOJOSARI - Erlin Kurnia Sari; Herlina Herlina (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
PT. Kerta Rajasa Raya is a manufacturing company engaged in the plastic sack manufacturing industry. The company uses Lohia 1 machines (Lohia 1 Extruder and Winder Machines) in producing semi-finished products, namely plastic yarn as the main ingredient for making plastic sacks. This Lohia 1 engine has different types of defects, which causes defects and production results that are not on target. Overall Equipment Effectiveness (OEE) is a measurement method to determine the extent of performance, as well as the quality of a machine or equipment. OEE is known as one of the implementations of Total Productive Maintenance (TPM). Measuring the level of performance effectiveness of the Lohia 1 engine at PT. Kerta Rajasa Raya in the period February 2022 to March 2022 the results obtained were somewhat inadequate according to the JIPM (Japan Institute Of Plant Maintenance) standard with a standard of 85%, while the effectiveness of the Lohia 1 engine, namely for February 2022 was 23% and March 2022 by 33%. So, the OEE percentage value is still below 85%